Chorus Song of the Indri (Indri indri: Primates, Lemuridae): Group Differences and Analysis of Within-group Vocal Interactions - Baker-Médard, Merrill S. A.; Baker, Myron C.; Logue, David M. (International journal of comparative psychology, 2013)
The loud chorus songs of the group-living lemur Indri indri are a striking feature of rainforest areas of eastern Madagascar. Despite some research on the conspicuous vocal display of the indri, two hypotheses have not been addressed: do groups differ in the acoustic properties of their songs, and is there evidence of coordinated singing between individuals within groups. We recorded and analyzed the songs of three indri groups to examine these two questions. To answer the first question, we made quantitative spectral measures on songs of the three groups and performed multivariate analyses of the acoustic features of the notes constituting the songs. Our results showed songs of the three groups differed significantly, although there was overlap between groups. To answer the second question, we classified note types and quantified their occurrence as overlapping and abutting pairs. We found non-random associations between sequential note types in all three indri groups. These associations were consistent among groups, suggesting that individuals follow consistent answering rules when contributing to choruses. Whether indris use acoustic group identifiers in management of behavioral strategies and how within-group coordinated note production might function remain unknown. We compare our results to a number of taxonomically diverse species that live in groups and broadcast chorus and duet vocal signals.